Effects of glioblastoma-derived extracellular vesicles on the functions of immune cells - Musatova, Oxana E.; Rubtsov, Yury P. (Frontiers in Cell and Developmental Biology, 2023)
Glioblastoma, the most aggressive variant among malignant neoplasms of the nervous system called gliomas, is characterized by astoundingly poor prognosis for patients. Combination of surgery, chemo- and radiotherapy in case of glioblastoma almost permanently results in rapid relapse in more aggressive and therapy resistant form. High heterogeneity partly accounts for glioblastoma resistance to therapy. Recently, it was demonstrated that extracellular vesicles produced by glioblastoma during apoptotic cell death can bind to surrounding cells and change their phenotype to more aggressive. Extracellular vesicles of glioblastoma participate also in establishment of immune suppressive microenvironment that protects glioblastoma from antigen-specific recognition and killing by T cells. In this review, we collected present data concerning characterization of extracellular vesicles from glioblastoma and study of their effects on different populations (naïve, effector T helpers, cytotoxic and regulatory) of the T cells. Assuming that tumor-infiltrating T cells operate in the surrounding of other immune cells, the analysis of recent reports of effects that glioblastoma and glioblastoma-derived vesicles impart on other immune cells are presented. We aimed at critical analysis of experimental evidence in order to conclude whether glioblastoma-derived extracellular vesicles are a major factor in immune evasion of these deadly tumors. Finally, we summarize clinical data linking survival prognosis and ability of glioblastoma to produce extracellular vesicles, and conclude that extracellular vesicles from glioblastoma should be seriously taken into consideration for non-invasive diagnostics and evaluation of therapy choice and prognosis.